2017
DOI: 10.1097/shk.0000000000000815
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Role and Diagnostic Value of Endogenous Host Defense Peptides in Adult and Neonatal Sepsis

Abstract: Innate defense peptides have been insufficiently evaluated as either diagnostic or prognostic biomarkers. In the future, evaluation of host defense peptides as septic biomarkers may employ a longitudinal design and consider a panel of multiple peptides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 89 publications
0
14
0
9
Order By: Relevance
“…AMPs work by inserting themselves into the bacterial membrane and forming pores, which result in the leakage of bacterial cytoplasmic content (76)(77)(78). They can also degenerate bacterial cytoplasmic structures and form extracellular net-like structures, which result in bacterial trapping (79).…”
Section: Paneth Cell Role In the Small Intestinementioning
confidence: 99%
“…AMPs work by inserting themselves into the bacterial membrane and forming pores, which result in the leakage of bacterial cytoplasmic content (76)(77)(78). They can also degenerate bacterial cytoplasmic structures and form extracellular net-like structures, which result in bacterial trapping (79).…”
Section: Paneth Cell Role In the Small Intestinementioning
confidence: 99%
“…Cathelicidin is one of the immunomodulatory proteins involved in the pathogenesis of sepsis [29]. Clinical studies have shown that human cathelicidin was 50% lower in critically ill patients with severe sepsis compared to non-septic patients and was further downregulated in septic shock [30].…”
Section: Discussionmentioning
confidence: 99%
“…Among septic patients, the plasma level of hBD‐1 was increased up more than hundred‐fold compared to healthy controls . However, investigators suggested that these innate immunity peptides were warranted further evaluation as septic biomarkers …”
Section: Discussionmentioning
confidence: 99%
“…Human beta-defensin-1 is an endogenous host defence peptide, which is a part of the family of antimicrobial peptides such as heparin-binding protein, lactoferrin, bactericidal/permeability increasing protein (BPI), hepcidin. [19][20][21] The above peptides have been studied in sepsis, (which is defined as a systemic host response to an infection leading to organ failure), as either diagnostic or prognostic biomarkers. Human hBD-1 expression is primarily constitutive while hBD-2 and hBD-3 are inducible during wounding or infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation